Alloy Nanocatalysts for the Electrochemical Oxygen Reduction (ORR) and the Direct Electrochemical Carbon Dioxide Reduction Reaction (CO2 RR) - Kim, Cheonghee (Advanced materials (Deerfield Beach, Fla.), 2019)
© 2018 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.